Brand loyalty and web service quality in a retail shoe store E-Commerce: An empirical exploration of the peruvian digital consumer - Cruzado-Pulido, Lorena Liceth; Rodríguez-Castillo, Pierina Andrea; Paredes-León, Francisco Jesús; Rodríguez-Castillo, María Soledad (LACCEI, 2024)
Digital shopping in Peru increased dramatically after the COVID-19 pandemic. In this new context, brand loyalty and the quality of Internet services have become key factors for the development of businesses that are beginning to digitize their commercial and marketing operations, as is the case of shoe stores. The main objective of this work is to demonstrate that there is a positive and significant level of dependence between the study constructs. For this purpose, a structured questionnaire was applied to 245 regular users of a shoe store in the city of Trujillo, Peru. The main findings show that both constructs are highly associated, and that changes in one affect the other in a reciprocal manner. In view of this, marketers should consider new strategies and digital management models that contribute to the development of local brands in the footwear retail industry.